2021
DOI: 10.5296/jsss.v8i2.18703
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisation of Psychological Contract: Definitions, Typologies and Measurement

Abstract: Background: Psychological contracts, and particularly the honouring of these contracts – are central to employee behaviour and organisational success. The interest of academics and practitioners in this construct is therefore understandable. However, due to the immense amount of information on the topic, a comprehensive review of the literature is necessary. Aim: The aim of this article is to present a critical review on the conceptualisation of the psychological contract, distilling and operationalising the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Using categorical moderator variables, Topa and Palaci [ 50 ] only confirmed that both the type of employment contract and the occupational category significantly moderate the relationships between psychological contract breach and neglect. Zhao and colleagues [ 48 ] confirmed that the content of the psychological contract breach (relational vs. transactional) significantly moderates the relationships with job satisfaction, organizational commitment, turnover intentions, and OCB. Topa, Morales, and Depolo [ 22 ] showed that the type of employment contract also moderates the relationships between psychological contract breach and organizational trust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using categorical moderator variables, Topa and Palaci [ 50 ] only confirmed that both the type of employment contract and the occupational category significantly moderate the relationships between psychological contract breach and neglect. Zhao and colleagues [ 48 ] confirmed that the content of the psychological contract breach (relational vs. transactional) significantly moderates the relationships with job satisfaction, organizational commitment, turnover intentions, and OCB. Topa, Morales, and Depolo [ 22 ] showed that the type of employment contract also moderates the relationships between psychological contract breach and organizational trust.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 potentially relevant systematic reviews were retrieved in full text. The further full-text examination of the retrieved papers allowed us to exclude the following: six duplicates, ten book reviews, one empirical study [ 31 ], one review focused on other work-related topics [ 32 ], one corrigendum article, one review focused on students’ psychological contract [ 33 ], and 17 theoretical reviews [ 6 , 23 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Finally, only 8 systematic reviews and meta-analyses met the inclusion criteria [ 22 , 24 , 27 , 28 , 49 , 50 , 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%